Sildenafil does not have a significant effect on the portal vein velocity, cross-sectional area, and congestion index in the dog - Tollefson, Christopher R.; Seitz, Marc A.; Natalini, Claudio C.; Lee, Alison M. (Frontiers in Veterinary Science, 2022)
In veterinary medicine, sildenafil is most frequently used to treat pulmonary hypertension, but has also been investigated and used as a treatment for congenital megaesophagus and ischemic infarcts. With the increasing use, the effects of sildenafil on the portal vasculature in the dog have not been previously evaluated. The purpose of this study was to evaluate the effects sildenafil has on the portal vasculature, which anecdotally may have caused decreased portal vein pressure in an adult dog. The ultrasound cross-sectional area of the aorta, cross-sectional area of the portal vein, and portal vein blood flow velocity were acquired in dogs prior to administration, and 45 minutes, 90 minutes, and 120 minutes after oral administration of sildenafil for the treatment of pulmonary hypertension. Thirteen dogs were enrolled in the study. No statistically significant difference was detected between all measured values and the congestion index at all time points. A trend was identified that demonstrated progressively lower portal vein velocity with each evaluation, but this was not significant. Although this study had a small sample size, sildenafil was not shown to have a significant effect on the size or blood flow velocity of the portal vasculature. The hepatic buffer system, designed to maintain a constant blood flow to the liver, may be a contributing factor, but further studies with a larger sample size will be required for further evaluation.